The use of open ended problem in developing mathematical reasoning ability of junior high school students on geometry - A Hasanah; K Karyati (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The mathematical ability of the students will only be the material that follows a series of procedures without knowing the meaning if the students' reasoning abilities are not depeloved. The purpose of research to describe the use of open ended problem in developing students' mathematical reasoning ability of junior high, especially on Geometry. This research is descriptive qualitative research. The instrument used in this research is test of mathematical reasoning ability based on open ended. The sample in this research is the students of grade 8 of Junior High School in Banjarmasin. Analysis of data by reducing data, presenting data and making conclusions. The results show that the use of open ended questions can develop students' mathematical reasoning ability of junior high school.